Mechanical and psychological effects of electoral reform - Jon H. Fiva; Olle Folke (Center for Economic Studies and ifo Institute (CESifo), 2011)
Duverger (1954) noted that changes in electoral systems will have two types of effects: mechanical effects, and reactions of political agents in anticipation of these, which he referred to as psychological effects. It is complicated to empirically separate the two effects since these occur simultaneously. In this paper we use a large set of counterfactual election outcomes to address this issue. Our application is based on a nationwide municipal electoral reform in Norway, which changed the seat allocation method from d'Hondt to modified Sainte-Lagüe. Even though this electoral reform is of a relatively small magnitude, we document substantial psychological effects.
Keywords: C10; H70; 330; Kommunalwahl; Wahlsystem; Reform; Wirkungsanalyse; Politiker; Psychologie; Schätzung; Norwegen